New lignans with neuroprotective activity from Adelostemma gracillimum. (June 2016) - Zhang, Jun; Guo, Shengjun; Chan, Kim W.; Tong, Estella P.S.; Fu, Guangmiao; Mu, Quanzhang; Ip, Fanny C.F.; Ip, Nancy Y.
Graphical abstract: Highlights: Extract of Adelostemma gracillimum is neuroprotective against excitotoxicity. Four novel and two known lignans, and five known acetophenones were isolated. Two novel and one known lignans are active in neuroprotection. These molecules hold potential for treating diseases marked with neuronal death. Abstract: Adelostemma gracillimum is an herb used as nourishing and roborant drugs and in the treatment of convulsions in children. To date, a few molecular constituents have been isolated from the root of this herb and chemically characterized, but their biological activities have never been reported. Here, we demonstrate that the crude extract of A. gracillimum (AGE) can protect primary cortical neurons against N -methyl-d -aspartate (NMDA)-induced cytotoxicity. Further fractionations of AGE led to the isolation of four novel lignans (1–4 ), two known lignans (5, 11 ), and five known acetophenones (6–10 ); their structures were elucidated by comparison with related literature, extensive analyses of NMR spectroscopy and high-resolution mass spectrometry. Of the eleven isolates, lignans2, 3 and5 exhibit significant neuroprotection against NMDA-induced cell death. This is the first report of isolating lignans with neuroprotective activity from A. gracillimum .